Multifunctional all‐nanofiber cloth integrating personal health monitoring and thermal regulation capabilities - Peng Wang; Guifen Sun; Shuaichuang Hua; Wei Yu; Chuizhou Meng; Qing Han; Jeonghyun Kim; Shijie Guo; Guozhen Shen; Yang Li (InfoMat)
Abstract Frequent heat waves and cold spells pose threats to human survival. Herein, we develop a multifunctional all‐nanofiber cloth with physiological signal monitoring and personal thermal management capabilities through facile fiber electrospinning and ink printing techniques. The double‐sided fabric mat of a thick carbon nanotube network with high solar absorption on top of a thermoplastic polyurethane nanofiber substrate with high solar reflectivity and mid‐infrared emissivity offers a contrary thermal management effect of heating or cooling by opposite wearing mode. The integrated fabric strain and temperature sensors for health status evaluation through monitoring physiological signals of respiration and body temperature. By wearing a T‐shirt tailored by the developed electronic cloth, the wearer's skin temperature can be actively regulated with cooling by 5.4°C and warming by 3.0°C in hot and cold environments compared to normal clothing, respectively. This platform can inspire further studies in wearable multifunctional permeable electronics.